Efficacy of octenidine against emerging echinocandin-, azole- and multidrug-resistant Candida albicans and Candida glabrata - Kathrin Spettel; Dominik Bumberger; Iris Camp; Richard Kriz; Birgit Willinger (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: Infections due to Candida species represent a serious threat to healthcare facilities. Only a few classes of antifungal agents are available, and the rapid emergence of (multi)drug resistance eliminates effective treatment options for successful patient outcome. Topically applied antiseptics may represent a suitable tool for infection control and local therapy. This study aimed to investigate the in vitro efficacy of the widely used antiseptic octenidine (OCT) against clinical isolates of emerging azole-, echinocandin- and multi-resistant Candida albicans and Candida glabrata. Methods: The antifungal activity of different concentrations of OCT ranging from 0.001% to 0.05% and of OCT-containing ready-to-use products was determined against well-characterised (multidrug) resistant C. albicans and C. glabrata isolates, including susceptible wild-type strains. Quantitative suspension tests were performed under “clean conditions” (0.3 g/L bovine serum albumin) and under “dirty conditions” (3 g/L albumin + 3 mL/L defibrinated sheep blood) as well as various contact times (30 s, 1 min, 2 min) according to EN13624:2013. Results: Even in the presence of a high organic load, pure OCT at 0.05% and a contact time of 30 s was fully effective for all Candida strains, with growth kinetics indicating a time- and concentration-dependent activity. Importantly, commercially available OCT-based products achieved the required reduction of ≥4 log10 for all Candida isolates under the most challenging dirty conditions within two minutes, which makes them suitable for routine clinical use. Conclusion: These results encourage consideration of the well-tolerated antiseptic molecule OCT in the eradication of emerging (multidrug) resistant C. albicans and C. glabrata.